Chronic kidney disease in adults with sickle cell trait: a systematic review and meta-analysis - Castro-Sesquen, Yagahira E.; Barboza Justiniano, Gelida; Aparcana-Granda, Diego J.; Aquino, Andres R.; Adelson, Pierre Luckens; Mondragón, Ronald D.; Kwagyan, John; Derebail, Vimal K.; Nouraie, Mehdi; Saraf, Santosh L.; Jerebtsova, Marina (Blood advances, 2025)
Sickle cell trait (SCT) may increase the risk of chronic kidney disease (CKD). We aimed to determine the pooled statistics of the association between SCT and CKD. Studies published up to May 2024 that were available on PubMed, Embase, Global Health Library, and Web of Science were screened. We included studies that reported odds ratios or hazard ratios (HRs) of CKD and/or end-stage renal disease (ESRD) and that compared adults with SCT to those without SCT. The risk of bias was evaluated using the Risk Of Bias In Nonrandomized Studies-of Exposures tool. The pooled SCT prevalence was calculated among patients with CKD/ESRD. A random-effects analysis was performed. Only studies with low or some concerns of bias were included, corresponding to 18 847 participants with SCT and 1 060 818 without SCT. Participants with SCT had higher odds of having an estimated glomerular filtration rate (eGFR) of ≤60 mL/min per 1.73 m2, proteinuria, and eGFR ≤60 mL/min per 1.73 m2 and/or proteinuria. The pooled prevalence of SCT among African American individuals with ESRD was 10%; however, the heterogeneity was very high (I2, 85.6%). There was a higher HR for ESRD in the studies that included both males and females than in the study that included only females, suggesting that males have a higher risk of ESRD. Controversial results were observed for the association of CKD with hypertension and diabetes. SCT increases the risk of developing CKD and ESRD. PROSPERO registration: CRD42021275274.